2005
DOI: 10.1136/pgmj.2004.023416
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute heart failure caused by sliding hiatus hernia

Abstract: The case is reported of a 75 year old woman who presented with recurrent nocturnal episodes of acute pulmonary oedema. The cause was uncertain as she had normal cardiothoracic ratio on chest radiography and normal left ventricular systolic and diastolic function by transthoracic echocardiogram. Another transthoracic echocardiogram was repeated when she was recumbent for an hour and had a full stomach. It showed a striking finding of severe left atrial compression by an external structure. Computed tomography o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 4 publications
0
33
1
1
Order By: Relevance
“…Siu et al reported on a hiatus hernia compressing the left atrium and leading to an increase of the capillary wedge pressure from 6 mm Hg while sitting upright to 18 mm Hg in supine position [2]. Hokamaki et al demonstrated dynamic electrocardiographic changes dependent from the gastric filling state in a patient with hiatal hernia [4].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Siu et al reported on a hiatus hernia compressing the left atrium and leading to an increase of the capillary wedge pressure from 6 mm Hg while sitting upright to 18 mm Hg in supine position [2]. Hokamaki et al demonstrated dynamic electrocardiographic changes dependent from the gastric filling state in a patient with hiatal hernia [4].…”
Section: Discussionmentioning
confidence: 97%
“…A major argument for elective surgery would be cardiac compression. However, the proof of the hemodynamic consequences of an intrathoracic stomach often remains a challenge [2,3]. Cardiovascular magnetic resonance (CMR) provides both anatomic and functional information and is characterized by highly reproducible image positioning, thus may be helpful in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Besides causing regurgitation and heartburn due to accompanying GERD, it may present with a wide spectrum of manifestations mimicking those of cardiovascular pathology such as postprandial syncope, angina-like chest pain, recurrent dyspnea and acute heart failure due to HH induced cardiac compression [11][12][13]. Further, HH may simulate the appearance of an intra-atrial mass on transthoracic echocardiography [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Akerlund et al [3], proposed the term hiatus hernia in 1926. The incidence of hiatal hernia increases significantly with age and it occurs in 10% of the adult population [4]. Children with this condition usually have it from birth (congenital).…”
Section: Discussionmentioning
confidence: 99%